Prenatal opioid exposure reprograms the behavioural response to future alcohol reward. (17th January 2022) - Grecco, Gregory G.; Haggerty, David L.; Reeves, Kaitlin C.; Gao, Yong; Maulucci, Danielle; Atwood, Brady K.
Abstract: As the opioid crisis has continued to grow, so has the number of infants exposed to opioids during the prenatal period. A growing concern is that prenatal exposure to opioids may induce persistent neurological changes that increase the propensity for future addictions. Although alcohol represents the most likely addictive substance that the growing population of prenatal opioid exposed will encounter as they mature, no studies to date have examined the effect of prenatal opioid exposure on future sensitivity to alcohol reward. Using a recently developed mouse model of prenatal methadone exposure (PME), we investigated the rewarding properties of alcohol and alcohol consumption in male and female adolescent PME and prenatal saline exposed (PSE) control animals. Conditioned place preference to alcohol was disrupted in PME offspring in a sex‐dependent manner with PME males exhibiting resistance to the rewarding properties of alcohol. Repeated injections of alcohol revealed enhanced sensitivity to the locomotor‐stimulating effects of alcohol specific to PME females. PME males consumed significantly more alcohol over 4 weeks of alcohol access relative to PSE males and exhibited increased resistance to quinine‐adulterated alcohol. Further, a novel machine learning model was developed to employ measured differences in alcohol consumption and drinking microstructure to reliably predict prenatal exposure. These findings indicate that PME alters the sensitivity to alcohol reward in adolescent mice in a sex‐specific manner and suggests prenatal opioid exposure may induce persistent effects on reward neurocircuitry that can reprogram offspring behavioural response to alcohol later in life. Abstract : Prenatal opioid exposure reprograms the behavioural response to future alcohol reward in sex‐dependent manner. Opioid‐exposed male offspring demonstrate increased alcohol consumption and aversion‐resistant intake, whereas opioid‐exposed female offspring exhibit robust conditioned place preference for alcohol and enhanced alcohol‐induced locomotor stimulation.